Operative management of pediatric empyema: a single center review - Aakriti Sharma (Society of Surgeons of Nepal, 2018)
Introduction: Empyema thoracis is an uncommon complication of childhood pneumonias but a common problem faced by a thoracic surgeon. Its management is still controversial, with a range of treatment options available and evolving gradually towards adoption of video-assisted thoracoscopic surgery (VATS) as the most commonly practiced one.